Direct Synthesis of Heavy Grignard Reagents: Challenges, Limitations, and Derivatization. Issue 63 (18th October 2018) - Koch, Alexander; Dufrois, Quentin; Wirgenings, Marino; Görls, Helmar; Krieck, Sven; Etienne, Michel; Pohnert, Georg; Westerhausen, Matthias
Abstract: The direct synthesis of organocalcium compounds (heavy Grignard reagents) by the reduction of organyl halides with activated calcium powder succeeded in a straightforward manner for organic bromides and iodides that are bound at sp 2 ‐hybridized carbon atoms. Extension of this strategy to alkyl halides was very limited, and only the reduction of trialkylsilylmethyl bromides and iodides with activated calcium allowed the isolation of the corresponding heavy Grignard reagents. Substitution of only one hydrogen atom of the methylene moiety by a phenyl or methyl group directed this reduction toward the Wurtz‐type coupling and the formation of calcium halide and the corresponding C−C coupling product. The stability of the methylcalcium and benzylcalcium derivatives in ethereal solvents suggests an unexpected reaction behavior of the intermediate organyl halide radical anions. Quantum chemical calculations verify a dependency between the ease of preparative access to organocalcium complexes and the C−I bond lengths of the organyl iodides. The bulkiness of the trialkylsilyl group is of minor importance. Chloromethyltrimethylsilane did not react with activated calcium; however, halogen‐exchange reactions allowed the isolation of [Ca(CH2 SiMe3 )(thf)3 (μ‐Cl)]2 . Furthermore, the metathetical approach of reacting [Ca(CH2 SiMe3 )I(thf)4 ] with KN(SiMe3 )2 and the addition of N, N, N′, N′′, N′′ ‐pentamethyldiethylenetriamine (pmdeta) allowed the isolation of heteroleptic [CaCH2 SiMe3 {N(SiMe3 )2 }(pmdeta)]. In the reaction of this derivative with phenylsilane, the trimethylsilylmethyl group proved to be more reactive than the bis(trimethylsilyl)amido substituent. Abstract : Organocalcium complexes : The success of the direct synthesis of heavy Grignard reagents, that is, organocalcium iodides, strongly depends on the C−I bond length of the organyl iodide radical anion that forms after the initial single electron transfer (SET) reaction, yielding either R‐Ca‐I and/or Wurtz‐type C−C coupling products (see scheme).